High-efficient microwave synthesis and characterisation of SrSnO3 - Bohnemann, Joerg; Libanori, Rafael; Moreira, Mario L.; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2009)
Strontium stannate (SrSnO3) nanostructures were obtained by microwave- assisted calcination of a SrSn(OH)(6) precursor powder. Compared to other conventional calcination methods mentioned in the literature, this procedure led to a remarkable decrease of the reaction time and the synthesis temperature owing to direct interaction of radiation with the material. X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM) and photoluminescence measurements were performed. A comparison of the characterisation results obtained by microwave and conventional methods was conducted, and differences concerning the properties of conventionally high-temperature calcined SrSnO3 from that obtained by microwave-assisted calcination were observed. Furthermore, two different morphologies (nanosticks and nanobrushes) were obtained by a variation of the concentration of the reactants. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: SrSnO3; Microwave; Nanostructures; Photoluminescence